O DISPOSITIVO DA MEDICALIZAÇÃO: UMA ANÁLISE DOS DISCURSOS PRODUZIDOS NA RELAÇÃO PODER/SABER MÉDICO, NUMA INSTITUIÇÃO ESCOLAR - BRODAY, ELIS REGINA (2023)
This study aimed to analyze the discourses produced in the medical power/knowledge relationship that consists of the medicalization device in a school institution. As an objective, we analyzed the discourses that produce the identification and referral process of the student who presents specific learning or behavioral conditions for psychoeducational assessment. This can lead to the provision of specialized educational services (AEE) for the target audience of special education (PAEE). Qualitative research was carried out, within the post-structuralist approach, based on the Foucauldian theoretical-methodological point of view in its archaeological and genealogical phases in a primary school in the city of Irati-PR. The subjects were three teachers of regular classes who work with PAEE and the teacher of the multipurpose resource room. In addition, a psychiatrist and a psychologist, who have already participated in psychoeducational evaluation processes, and a student's mother, who has a son diagnosed with attention deficit disorder (ADHD) and receives AEE in the multipurpose resource room. Data collection included semi-structured interviews with the research subjects and document analysis of Psychoeducational Evaluation Reports in the School Context and School Performance Reports of two PAEE students. The data analysis was based on discourse analysis (DA), and to build the categories for the DA of the data collected in the field, the DA of a lecture given by a pediatrician, specialized in child neurology, available on the platform Youtube, of public access, was carried out. For the theoretical and methodological basis of the DA, we used some of the tools provided by Foucault in his works and by Fisher (1995; 2001; 2003; 2013). The study found that the power relationship between medical, psychological, and pedagogical knowledge is constantly updated through school practices in everyday school life. This relationship enables the production of discourses from different fields of knowledge and constitutes the school subject. As a disciplinary institution, the school is organized to classify these subjects and develop strategies of normalization for those with learning and behavioral characteristics. Thus, the medicalization of education is a reality experienced in school.